Erwinia asparaginase (crisantaspase) increases plasma levels of serine and glycine - Bollino, Dominique; Claiborne, J. Preston; Hameed, Kanwal; Ma, Xinrong; Tighe, Kayla M.; Carter-Cooper, Brandon; Lapidus, Rena G.; Strovel, Erin T.; Emadi, Ashkan (Frontiers in Oncology, 2022)
The impact of asparaginases on plasma asparagine and glutamine is well established. However, the effect of asparaginases, particularly those derived from Erwinia chrysanthemi (also called crisantaspase), on circulating levels of other amino acids is unknown. We examined comprehensive plasma amino acid panel measurements in healthy immunodeficient/immunocompetent mice as well as in preclinical mouse models of acute myeloid leukemia (AML) and pancreatic ductal adenocarcinoma (PDAC) using long-acting crisantaspase, and in an AML clinical (NCT02283190) study using short-acting crisantaspase. In addition to the expected decrease of plasma glutamine and asparagine, we observed a significant increase in plasma serine and glycine post-crisantaspase. In PDAC tumors, crisantaspase treatment significantly increased expression of serine biosynthesis enzymes. We then systematically reviewed clinical studies using asparaginase products to determine the extent of plasma amino acid reporting and found that only plasma levels of glutamine/glutamate and asparagine/aspartate were reported, without measuring other amino acids changes post-asparaginase. To the best of our knowledge, we are the first to report comprehensive plasma amino acid changes in mice and humans treated with asparaginase. As dysregulated serine metabolism has been implicated in tumor development, our findings offer insights into how leukemia/cancer cells may potentially overcome glutamine/asparagine restriction, which can be used to design future synergistic therapeutic approaches.